HUBUNGAN KARAKTERISTIK PERAWAT DENGAN KEPATUHAN PRINSIP BENAR PEMBERIAN OBAT SECARA INTRAVENA DI RUANG RAWAT INAP RUMAH SAKIT SWASTA KOTA BANJARMASIN - Nursery, Septi Machelia Champaca (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2023)
Failure of the treatment process by administering intravenous drugs to patients has the potential to endanger patient safety. PMKP reports regarding drug administration errors in a Private Hospital in Banjarmasin City were 3 cases in 2018, 4 cases in 2019, 2 cases in 2020, and one case in 2021. The research objective was to determine the relationship between nurse characteristics and adherence to the principles of correct intravenous drug administration. The research method used a cross-sectional research model. The research was conducted at a private hospital in the city of Banjarmasin. The sampling technique consisted of cluster sampling and simple random sampling with a total of 35 samples. The data collection technique was an observation sheet. Data analysis used univariate with frequency distribution and bivariate with Spearman Rank and Chi-Square. The results showed that 23 respondents (65.7%) were included in the category of obedient nurses, and from the spearman ranking results obtained a comparison value of age compliance 0.091 > 0.05 with a correlation coefficient of 0.290. The Chi-Square results for gender with adherence were 0.327 > 0.05 with a correlation coefficient of 2.029. Education results from Spearman Rank 0.465 > 0.05 with a correlation coefficient of 0.128, and length of work with obedience 0.005 <0.05 with a correlation coefficient of 0.467. Nurses who have diverse characteristics are expected to be able to carry out and work together to carry out the principles of correct intravenous drug administration, especially double examination, asking about drug allergies, and patient complaints before and after drug administration, checking drug expiration dates, identifying patients, recording patient complaints, and reasons for drug refusal. Keywords: characteristics of nurses, nurse compliance, correct principles of drug administration